CXCR5+PD1+ICOS+ Circulating T Follicular Helpers Are Associated With de novo Donor-Specific Antibodies After Renal Transplantation - Danger, Richard; Chesneau, Mélanie; Delbos, Florent; Le Bot, Sabine; Kerleau, Clarisse; Chenouard, Alexis; Ville, Simon; Degauque, Nicolas; Conchon, Sophie; Cesbron, Anne; Giral, Magali; Brouard, Sophie (Frontiers in Immunology, 2019)
Donor-specific anti-HLA antibodies (DSAs) are a major risk factor associated with renal allograft outcomes. As a trigger of B cell antibody production, T follicular helper cells (Tfhs) promote DSA appearance. Herein, we evaluated whether circulating Tfhs (cTfhs) are associated with the genesis of antibody-mediated rejection. We measured cTfh levels on the day of transplantation and one year after transplantation in blood from a prospective cohort of 237 renal transplantation patients without DSA during the first year post-transplantation. Total cTfhs were characterized as CD4+CD45RA-CXCR5+, and the three following subsets of activated cTfh were analyzed: CXCR5+PD1+, CXCR5+PD1+ICOS+ and CXCR5+PD1+CXCR3-. Immunizing events (previous blood transfusion and/or pregnancy) and the presence of class II anti-HLA antibodies were associated with increased frequencies of activated CXCR5+PD1+, CXCR5+PD1+ICOS+ and CXCR5+PD1+CXCR3- cTfh subsets. In addition, ATG-depleting induction and calcineurin inhibitor treatments were associated with a relative increase of activated cTfh subsets frequencies at one year post-transplantation. In multivariate survival analysis, we reported that a decrease in activated CXCR5+PD1+ICOS+ at one year after transplantation in the blood of DSA-free patients was significantly associated with the risk of developing de novo DSA after the first year (p=0.018, HR =0.39), independently of HLA mismatches (p=0.003, HR =3.79). These results highlight the importance of monitoring activated Tfhs in patients early after transplantation and show that current treatments cannot provide early, efficient prevention of Tfh activation and migration. These findings indicate the need to develop innovative treatments to specifically target Tfhs to prevent DSA appearance in renal transplantation.